The Analysis of Psychological Aspect of Main Character in Cruella Movie - Natalia Angelina Amnesi; I Made Perdana Skolastika (CV Wahana Publikasi, 2023)
This study discusses the characterization of the main character in Cruella by Craig Gillespie. This study aims to analyze the behaviour of the Cruella movie and identify the main character. The data are taken from the Cruella film from scenes and dialogues containing the Psychological Aspects. The data were analyzed using the theory proposed by Bernhardt (1953) to identify Psychological Aspects of Human Motivation. In this study, data were collected using the observation method. Data were analyzed using qualitative methods and presented descriptively. The results of this study obtained 24 data related to the Psychological Aspects of Human Motivation experienced by the main character. The Aspect of want dominates the main character in the Cruella movie because of the conflicts and incidents experienced by the main character as the emotional side of the main character makes her want everything that can relieve her anger and fulfill her goals. In conclusion, the psychological aspect of human motivation has a significant influence on a person’s actions that can affect a person’s psychological aspects.